Surgical alternatives for maxillary sinus elevation: Integrative literature review (Research, Society and Development, 2024)
Aim: This study aims to present an integrative review of the literature on surgical alternatives for maxillary sinus elevation. Methodology: This review was carried out through a bibliographic survey, through an online search in the PubMed and Virtual Health Library databases. The following descriptors indexed in Mesh (Medical Subject Headings) “Augmentations”, “Antrum”, “Bone” and “Bone Graft” were used in this research, interconnected using the Boolean descriptor “AND”. The period analyzed corresponded to the last 14 years. Results: The literature presents several surgical alternatives for each stage of the maxillary sinus elevation procedure, ranging from access techniques to osseodensification. Conclusion: Although there is a range of surgical alternatives for maxillary sinus elevation, there is no consensus in the literature regarding the best technique for each stage of the procedure. Therefore, it is up to the Surgeon to decide together with the patient the treatment plan with greater predictability.